The relationship between the strength of religious faith and spirituality in relation to post-traumatic growth among nurses caring for COVID-19 patients in eastern Poland: a cross-sectional study - Nowicki, Grzegorz Józef; Schneider-Matyka, Daria; Godlewska, Iwona; Tytuła, Andrzej; Kotus, Marzena; Walec, Monika; Grochans, Elżbieta; Ślusarska, Barbara (Frontiers in Psychiatry, 2024)
Introduction The COVID-19 pandemic had forced intensive care unit (ICU) nurses to adapt to extreme conditions in a short period of time. This resulted in them experiencing extremely stressful situations. The aim of this study was to assess the relationship between post-traumatic growth (PTG) and religiosity and spirituality (R/S) among nurses caring for COVID-19 patients in intensive care during the pandemic. Materials and methods 120 nurses working in Lublin, eastern Poland, participated in the cross-sectional study. The questionnaire was made up of three standardised tools: The Post-Traumatic Growth Inventory, The Santa Clara Strength of Religious Faith Questionnaire, The Spiritual Attitude and Involvement List. Results In terms of spirituality, the study group of nurses achieved the highest score in the Connectedness with Nature subscale (4.37 ± 1.07), while the strength of religious beliefs had a positive correlation with post-traumatic growth only in the Spiritual changes subscale (r = 0.422, p < 0.001). The following dimensions of spirituality were significantly correlated with post-traumatic growth in the multi-factor model that included religiosity and spirituality: Transcendent experiences, Spiritual activities, Meaningfulness, Acceptance, and Trust. We saw that increase in the assessment of the Transcendent experiences, Meaningfulness and Trust subscales significantly mirrors increase in post-traumatic growth, while increase in the assessment of the Spiritual activities and Acceptance subscales significantly mirrors decrease in post-traumatic growth. The above variables explained up to 44% of the dependent variable. Conclusion Both religiosity and spirituality were significantly associated with post-traumatic growth in the group of ICU nurses, but spirituality appears to have played a larger role. Our findings support the value and significance of the development of spiritual and religious identity as a means of enhancing positive psychological changes in the face of traumatic events.